Beban Kerja Front Desk Agent pada Masa New Normal di TRC Bali - Netrina Putri Alfareda Palla; I Wayan Seniartha; Anak Agung Istri Ratna Sari Wulan (Program Studi Manajemen Divisi Kamar, 2022)
This study is about the workload of Front Desk Agents during the new normal period at TRC Bali, to know how the workload of Front Desk Agents during the new normal period at TRC Bali. The data of this research were obtained through interview and observation techniques, with the data analysis used was quantitative descriptive technique. With the theory put forward by Moekijat regarding Work Load Analysis and Mangkunegara regarding Work Force Analysis. The results of the analysis show that the workload of front desk agents during the new normal period is high. The workload analysis of 8.98 was rounded up to 9 people, and the work force analysis of 9.14 and rounded up to 9 people. From these calculations, it can be seen that the number of front desk agents is 9 people, while in reality there are only 4 people. Suggestions from the authors related to this research are to calculate the workload clearly and well and add a workforce of 5 people so that the front desk agent does not have an overload of work so that they can provide maximum service.